Estudo de sistema de medição de sinal de tensão sem contato e sem aterramento, em média tensão - Vogel, Ederson Paulo (Universidade do Vale do Rio dos Sinos, 2017)
The measurement of current and voltage (as well as the indexes derived from them) in the electricity distribution network becomes more and more necessary in the present day. The power concessionaires seek to distribute to their customers, reliability and stability in the supply of this energy with admissible levels of quality established by the regulatory body of the electric system. In order to carry out a study of a signal measurement system without the need to disconnect medium voltage electrical conductors and without using a ground reference, the present work describes a methodology based on the analysis of the electric field generated by these Conductors to store energy and infer a voltage in a capacitor of parallel plates with certain characteristics, situated at a certain distance from them. With the use of computational simulation through software based on the Maxwell equations, it is possible to obtain values of the potential difference for systems with single-phase topology and to correlate it with the voltage that generated these electric fields. For a network with two-phase and three-phase topology, it was not possible to perform this correlation, however there is room to apply digital seeding techniques of sources with the purpose of discriminating the contribution of each phase in the sensor element.
Keywords: Qualidade de energia elétrica; Medição de forma de onda da média tensão monofásica; Campo elétrico; Quality of electric power; Measurement of single-phase medium voltage waveform; Electric field; ACCNPQ::Engenharias::Engenharia Elétrica